Proteomic Study of the Survival and Resuscitation Mechanisms of Filamentous Persisters in an Evolved Escherichia coli Population from Cyclic Ampicillin Treatment - Jordy Evan Sulaiman (American Society for Microbiology, 2020)
ABSTRACT Through adaptive laboratory evolution (ALE) experiments, it was recently found that when a bacterial population was repetitively treated with antibiotics, they will adapt to the treatment conditions and become tolerant to the drug. In this study, we utilized an ampicillin-tolerant Escherichia coli population isolated from an ALE experiment to study the mechanisms of persistence during ampicillin treatment and resuscitation. Interestingly, the persisters of this population exhibit filamentous morphology upon ampicillin treatment, and the filaments are getting longer over time. Proteomics analysis showed that proteins involved in carbohydrate metabolism are upregulated during antibiotic treatment, in addition to those involved in the oxidative stress response. Bacterial SOS response, which is associated with filamentation, was found to be induced on account of the increasing expression of RecA. Measurement of endogenous reactive oxygen species (ROS) revealed that the population have ∼100-fold less ROS generation under ampicillin treatment than the wild type, leading to a lower mutagenesis rate. Single-cell observations through time-lapse microscopy show that resuscitation of the filaments is stochastic. During resuscitation, proteins involved in the tricarboxylic acid (TCA) cycle, glyoxylate cycle and glycolytic processes, and ATP generation are downregulated, while ribosomal proteins and porins are upregulated in the filaments. One particular protein, ElaB, was upregulated by over 7-fold in the filaments after 3 h of resuspension in fresh medium, but its expression went down after the filaments divided. Knockout of elaB increased persistence on wild-type E. coli, and upon resumption of growth, mutants lacking elaB have a higher fraction of small colony variants (SCVs) than the wild type. IMPORTANCE Persisters are a subpopulation of cells with enhanced survival toward antibiotic treatment and have the ability to resume normal growth when the antibiotic stress is lifted. Although proteomics is the most suitable tool to study them from a system-level perspective, the number of persisters that present naturally is too few for proteomics analysis, and thus the complex mechanisms through which they are able to survive antibiotic stresses and resuscitate in fresh medium remain poorly understood. To overcome that challenge, we studied an evolved Escherichia coli population with elevated persister fraction under ampicillin treatment and obtained its proteome profiles during antibiotic treatment and resuscitation. We discovered that during treatment with ampicillin, this tolerant population employs an active oxidative stress response and exhibits lower ROS levels than the wild type. Moreover, an inner membrane protein which has implications in various stress responses, ElaB, was found to be highly upregulated in the persisters during resuscitation, and its knockout caused increased formation of small colony variants after ampicillin treatment, suggesting that ElaB is important for persisters to resume normal growth.